WORD FORMATION PROCESSES FOUND IN JOKOWI NEWS OF JAKARTA POST NEWSPAPER - FATMALA, VIVIN DWI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Word Formation Processes, Jakarta Post Newspaper, Jokowi News.The writer is interested in conducting a study of word formation processes found in Jokowi news of Jakarta Post newspaper. The aim of this study is to investigate the words formation found in news. There are two problems of the study. (1) What are the word formation processes found in Jokowi news of Jakarta Post newspaper. (2) What is the most word formation process commonly used in Jokowi news of Jakarta Post newspaper. The finding of this study is expected to give a useful reference for the students of Study Program of English to improve a better understanding of English word formation processes.The writer used the theory of Yule (2010) to analyze the data in this study. The writer took 16 Jokowi news in Jakarta Post as the data. This study used qualitative approach because the data are in the form of text.The finding shows that there were 104 words included in word formation process’ theory by Yule (2010). The writer found 10 words of borrowing, 13 words of conversion, 9 words of acronym, 2 words of clipping, 2 words of multiple process,35 words of derivation, 21 words of compounding, 2 word of coinage, 1 word of blending, and 6 words of backformation. This study reveals that derivation is the most word formation commonly used in Jokowi news of Jakarta Post newspaper.The writer would like to invite further researcher to conduct further and better study. The next researcher can try to find out theory based on the different expert. The writer also suggests for the next researchers who are interested in doing furtherresearch in this area to conduct the research with more variation in data collection.